Voice and political engagement: Evidence from a natural field experiment - Anselm Hager; Lukas Hensel; Christopher Roth; Andreas Stegmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We conduct a natural field experiment with a major European party to test whether giving party supporters the opportunity to voice their opinions increases their engagement in the party's electoral campaign. In our experiment, the party asked a random subset of supporters for their opinions on the importance of different topics. Giving supporters more opportunities to voice their opinions increases their engagement in the campaign as measured using behavioral data from the party's smartphone application. Survey data reveals that our voice treatments also increase other margins of campaign effort as well as perceived voice. Our evidence highlights that parties can increase their supporters' investment in the democratic process by implementing policies that increase their voice.
Keywords: D8; P16; 330; Political engagement; Inclusion; Voice; Agency; Natural Field Experiment; Canvassing